Factors affecting success of galls of Aditrochus coihuensis (Hymenoptera: Pteromalidae) = Factores que afectan el éxito de las agallas de Aditrochus coihuensis (Hymenoptera: Pteromalidae) - Nilsson, Michael; Corley, Juan Carlos; Anderbrant, Olle (Sociedad Entomológica Argentina, 2019)
Galls of Aditrochus coihuensis (Hymenoptera: Pteromalidae) were collected from their host tree, the southern beech Nothofagus dombeyi, near San Carlos de Bariloche, Argentina, during the spring of 2007. Galls were carefully examined and classifi ed as successful or unsuccessful based on insect remains and emergence-hole diameter. Gall properties (diameter, wall thickness, chamber diameter, wall toughness) were measured and compared between successful galls and unsuccessful (parasitized) galls. Gall diameter and wall thickness were strongly correlated and thick walls seem to function as a protection against parasitoids. Parasitoids (Torymidae) that were found within some galls had an ovipositor length shorter than wall thickness of fully developed galls. Most likely, parasitoids attack galls only during a limited time when the wall is thin enough. Wall toughness did not seem to infl uence gall success. In total 67% of the galls suffered from parasitoids. Inquilines (Curculionidae) were found within some gall walls, with preference for larger galls and for those with thicker walls. Traces of potential bird or wasp predation were also found in a few specimens. Our present fi ndings contribute original descriptive information on these galls. Overall, our results lend further support on the potential importance of natural enemies on gall evolution.